Constitutive Modeling of the Tensile Behavior of Recycled Polypropylene-Based Composites - Kui Wang (137551) (2019)
The effect of reprocessing on the quasi-static uniaxial tensile behavior of two commercial polypropylene (PP)-based composites is experimentally investigated and modeled. In particular, the studied materials consist of an unfilled high-impact PP and a talc-filled high-impact PP. These PP composites are subjected to repeated processing cycles, including a grinding step and an extrusion step to simulate recycling at the laboratory level, the selected reprocessing numbers for this study being 0, 3, 6, 9, and 12. Because the repeated reprocessing leads to thermo-mechanical degradation by chain scission mechanisms, the tensile behavior of the two materials exhibits a continuous decrease of elastic modulus and failure strain with the increasing amount of reprocessing. A physically consistent three-dimensional constitutive model is used to predict the tensile response of non-recycled materials with strain rate dependence. For the recycled materials, the reprocessing effect is accounted by incorporating the reprocessing sensitive coefficient into the constitutive model for Young’s modulus, failure strain, softening, and hardening equations. Our predictions of true stress—true strain curves for non-recycled and recycled 108MF97 and 7510—are in good agreement with experimental data and can be useful for industries and companies which are looking for a model able to predict the recycling effect on mechanical behavior of polymer-based materials. Other Information Published in: Materials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ma12152419